Proceedings of the 20th International Seminar on Paste and Thickened Tailings 2017
DOI: 10.36487/acg_rep/1752_41_guang
|View full text |Cite
|
Sign up to set email alerts
|

Application of in-line polymer addition for tailings disposal-learning and challenges part II

Abstract: The use of polyacrylamide-based high-molecular-weight polymer addition at the tailings storage facility (TSF) discharge locations has gained considerable interest in recent years. The intended result of implementing this technique is to have tailings slurry release clear water and create a steepened beach, compared to a conventional tailings slurry disposal method. This paper will focus on a study of a typical iron ore project which required improved water recovery. It has been suggested in previous studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This will result a rapid separation of water from the tailings solids immediately downstream of the plunge pool that typically exists at the tailings discharge location. The method of applying polymers to treat tailings is known as in-line flocculation or in-line polymer addition (Wells and Riley, 2007., Bembrick, 2008., Wells et al 2011., Mizani, 2013., Guang et. al, 2014., Riley and Utting, 2014., Guang and Longo, 2017., Costine et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will result a rapid separation of water from the tailings solids immediately downstream of the plunge pool that typically exists at the tailings discharge location. The method of applying polymers to treat tailings is known as in-line flocculation or in-line polymer addition (Wells and Riley, 2007., Bembrick, 2008., Wells et al 2011., Mizani, 2013., Guang et. al, 2014., Riley and Utting, 2014., Guang and Longo, 2017., Costine et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The method of applying polymers to treat tailings is known as in-line flocculation or in-line polymer addition (Wells and Riley, 2007., Bembrick, 2008., Wells et al 2011., Mizani, 2013., Guang et. al, 2014., Riley and Utting, 2014., Guang and Longo, 2017., Costine et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In Guang et al (2014) the initial polymer selection testwork was presented. Since then, this mine site began using in-line polymer addition at their TSF.…”
Section: Introductionmentioning
confidence: 99%
“…They (ibid) have also reported that significant recovery of structure can occur as material flows away from the deposition point. Guang et al (2014) conducted several testing programmes for the application in-line polymer addition for tailings disposal and reported that polymer selection is both site-specific and operation-specific. They also reported yield stress reduction as the tailings flowed across the tailings beach.…”
Section: Introductionmentioning
confidence: 99%